Visible to infrared energy conversion in Pr3+-Yb3+ co-doped fluoroindate glasses - Borrero-González, L. J.; Galleani, G. [UNESP]; Manzani, D. [UNESP]; Nunes, L. A O; Ribeiro, Sidney José Lima [UNESP] (Elsevier, 2013)
Processes involving visible to infrared energy conversion are presented for Pr3+-Yb3+ co-doped fluoroindate glasses. The emission in the visible and infrared regions, the luminescence decay time of the Pr 3+:3P0 → 3H4 (482 nm), Pr3+:1D2 → 3H6 (800 nm), Yb3+:2F5/2 → 2F 7/2 (1044 nm) transitions and the photoluminescence excitation spectra were measured in Pr3+ samples and in Pr3+-Yb 3+ samples as a function of the Yb3+ concentration. In addition, energy transfer efficiencies were estimated from Pr3+: 3P0 and Pr3+:1D2 levels to Yb3+:2F7/2 level. Down-Conversion (DC) emission is observed due to a combination of two different processes: 1-a one-step cross relaxation (Pr3+:3P0 → 1G4; Yb3+:2F7/2 → 2F5/2) resulting in one photon emitted by Pr3+ (1G4 → 3H5) and one photon emitted by Yb3+ (2F7/2 → 2F5/2); 2-a resonant two-step first order energy transfer, where the first part of energy is transferred to Yb3+ neighbor through cross relaxation (Pr3+:3P0 → 1G4; Yb3+:2F7/2 → 2F5/2) followed by a second energy transfer step (Pr 3+:1G4 → 3H4; Yb3+:2F7/2 → 2F5/2). A third process leading to one IR photon emission to each visible photon absorbed involves cross relaxation energy transfer (Pr3+: 1D2 → 3F4; Yb 3+:2F7/2 → 2F5/2). © 2013 Elsevier B.V. All rights reserved.
Keywords: Fluoroindate glasses Frequency down-conversion Lanthanides Energy transfer